COMPARISONS OF THE PROFITABILITY VALUE OF THE BROILER FARMING ON THREE MODELS OF PARTNERSHIP SYSTEM WITH CLOSE HOUSE SYSTEM IN MALANG REGENCY - Julian Adam Rijal; Amam Amam (UPT Penerbitan Universitas Jember, 2017)
Three models of partnership system with close house system was used in this researchconsists of : 1) profit sharing, 2) sub-contract, and 3) management fee. The aim of thisresearch was to (a) formulated production cost and cost structure was used for producingchicken meat, (b) analyzed profitability value based : GPM (Gross Profit Margin), NPM (NetProfit Margin), ROA (Return of Assets), and ROE (Return of Equity). The method of thisresearch that is case study. Sampling data was used consists of survey method, observation,and direct interview with farmers. The result showed that (a) production cost has spent byfarmers for producing one kilogram at partnership system with profit sharing system on Rp.21.006, sub-contract system on Rp. 21.132, and management fee system on Rp. 14.610; (b)GPM value at partnership system with profit sharing system on 7 %, sub-contract system on3% and management fee system on 11%; NPM value at partnership system with profitsharing system on 7,01 %, sub-contract system on 3,20 % and management fee system on10,74%; ROA value at partnership system with profit sharing system on 6,59 %, sub-contractsystem on 5,93% and management fee system on 19,42%; ROE value at partnership systemwith profit sharing system on 14,15 %, sub-contract system on -5,63% and management feesystem on 18,47%.